Addressing Fragmentation: Integrated Waste Management Synergy Policy at the Green Campus of the State Islamic University of Jakarta - Sri Mulyati (AMUYA: JOURNAL OF MANAGEMENT, 2026)
This policy paper examines the weak implementation of the Green Campus program at UIN Syarif Hidayatullah Jakarta, which is caused by the lack of synergy between units and faculties in realizing an efficient and sustainable Integrated Solid Waste Management (ISWM) system. Analysis using the USG (Urgency, Seriousness, Growth) method identified that the Green Campus Program Performance is difficult to evaluate objectively as a top priority policy issue (Total Score 15). The root of the problem, mapped using a Fishbone Diagram, is the absence of Environmental Performance Accountability Standards (SAKL), limited human resource capacity, and ad hoc technology procurement policies. To select the best solution, a comparative policy analysis based on William N. Dunn's theory was conducted on five alternatives. The results recommend the Rector's Regulation on the Integrated Environmental Management System (SML) as the most effective intervention (Score 17). This regulation should serve as the primary legal umbrella to eliminate governance fragmentation, mandate the Plan-Do-Check-Act (PDCA) cycle, and integrate KPI development obligations and Monev resource allocation across all units.